Sleep Surgery Variations: The Evolution of Surgery for Obstructive Sleep Apnea at an Academic Hospital. (2nd September 2014) - Russell, Jonathon O; Anderson, Jared; Bae, Charles; Kominsky, Alan
Abstract : Objectives: (1) Identify surgeon dependent and temporal variations in indications and surgical interventions for obstructive sleep apnea (OSA) at a tertiary academic hospital. (2) Clarify if volume of sleep surgeries performed affects outcomes. (3) Determine if surgical volume correlates with technical variation (ie, do surgeons who perform more surgeries for OSA perform additional procedures beyond uvulopalatopharyngoplasty [UPPP]). Methods: Retrospective chart review: Adult patients who had undergone UPPP since 2003 and had electronic medical records available were included. Quality of life (QOL) instruments included in the electronic medical record such as the Epworth Sleepiness Scale (ESS) and the Functional Outcomes of Sleep Questionnaire (FOSQ) were included. Pre‐ and postoperative results were compared using standard statistical analysis. Results: A total of 247 patients met inclusion criteria. Median AHI of all patients with available postoperative PSG decreased from 39.4 to 21.4. Patients of high‐volume surgeons (>10 UPPP per year) were more likely to have a lower preoperative Friedman score ( P <. 02), complete a postoperative PSG ( P <. 0001 by the 2‐tailed Fisher exact test), have a decreased postoperative ESS ( P <. 01), and have a PSG completed sooner after surgery ( P <. 01). Postoperative AHI and change in AHI did not differ between groups, however ( P =. 21 and P =. 14, respectively). Conclusions: UPPP contributes to objective improvement in PSG measures and quality of life. Nuances in patient selection and patient management are apparent between high volume surgeons and others, and may contribute to quality of life variations. Standardization of patient selection, timing of postoperative PSG, and increased utilization of QOL instruments may improve QOL outcomes among surgeons who do not perform UPPP regularly.